Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Consider the Legendre differential equation $$ (1-x^2) y'' - 2xy' + n(n+1)y = 0 $$ Then its solution is given by $$ y = c_1 P_n (x) + \text{an infinite series} $$ In fact $y = c_1 P_n (x) + c_2 Q_n (x) $ where $P_n$ is Legendre polynomials and $Q_n $ is Legendre function of the second kind. Here I want to prove that 'an infinite series' above can be written by $c_2 Q_n (x)$ for some constant $c_2$.

share|improve this question
    
You should see this. –  J. M. Jul 29 '12 at 4:15
    
@J.M. Thank you J.M., this proof is what I wanted. –  Ann Jul 29 '12 at 4:31

1 Answer 1

The infinite series you are talking about stems from the recurrence relation that can be derived when solving the Legendre differential equation: plugging in $$y = \sum_{j=0}^{\infty}a_jx^j $$ into $$[(1-x^2)y']' + n(n+1)y = 0$$ you get $$\frac{a_{k+2}}{a_k} = \frac{k(k+1) - n(n+1)}{(k+1)(k+2)}$$ Obviously, this leads to separate solutions with all even or all odd powers of $x$. When $n$ is even, then starting with $a_0 \not= 0$, the series terminates and you get (a multiple of) $P_n$. The same holds for odd $n$ starting with $a_1 \not= 0$. But when n is even and we start with $a_1 \not= 0$, then the series does not terminate. For instance, for $n=0$, we get $$\frac{a_{k+2}}{a_k} = \frac{k(k+1)}{(k+1)(k+2)} = \frac{k}{k+2}$$ which clearly leads to (taking $a_1=1$) $$y= \sum_{k=0}^{\infty}\frac{1}{2k+1}x^{2k+1}$$ Now, as $$ln(1+x) = \sum_{j=0}^{\infty}\frac{(-1)^{j+1}}{j}x^j$$ it is easy to derive \begin{equation} \begin{split} ln(\frac{1+x}{1-x}) &= ln(1+x) - ln(1-x) \\ &=\sum_{j=0}^{\infty}\frac{(-1)^{j+1}}{j}x^j + \sum_{j=0}^{\infty}\frac{x^j}{j} \\ &=\sum_{j=0}^{\infty}\frac{(-1)^{j+1} + 1}{j}x^j \\ &= 2x + 2\frac{x^3}{3} + 2\frac{x^5}{5} + ... \end{split} \end{equation} which is twice what we are looking for. So $$Q_0(x) = \frac{1}{2} ln(\frac{1+x}{1-x})$$ Similarly, $$Q_1(x) = \frac{x}{2} ln(\frac{1+x}{1-x}) - 1$$ And the rest of the $Q_n$ can then be determined by using the recurrence relation $$(n+1)Q_{n+1}(x) = (2n+1)xQ_n(x) - nQ_{n-1}(x)$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.